O efeito de fatores institucionais no incremento da arrecadação do ISSQN nos municípios de médio e grande porte do Nordeste - Couto, Felipe Mascarenhas (2018)
The Tax on Services of any nature, is the main tax tribute collected by most of the municipalities of the Northeast, it is interesting to discuss the factors that drive their collection, without there being an immediate burden on the population (rate increase). The objective of this work is to analyze the effect of institutional factors on the collection of the Tax on Services of any Nature (ISSQN) in the medium and large municipalities of the Northeast region. Therefore, the vision of the new institutional economy, which conceptualizes the institutions and presents the institutional factors that will promote the growth of a country or region, will be presented as a theoretical reference. The other part of the theoretical framework presents the concepts of taxation theory until the characteristics and transformations of the Brazilian tax system, the municipal tax systems, and, in particular, the ISSQN, are reached. As empirical strategy, panel data analysis was used, measuring the impact of institutional factors through dummy variables. It was observed that the institutional factors, besides guaranteeing good institutional relations, also affects the collection, being that in the majority of the studied factors, in a positive way.